TRFolder: computational prediction of novel telomerase RNA structures in yeast genomes. (1st January 2011) - Guo, Leilei; Zhang, Dong; Wang, Yingfeng; Malmberg, Russell L.; McEachern, Michael J.; Cai, Liming
The identification of Telomerase RNAs (TRs) has been difficult owing to their rapid evolutionary divergence. The common core structure found in all known TRs contains a pseudoknot and a triple helix, which are beyond the capability of existing RNA-structure-profiling techniques. We describe a novel approach to predict the structure of key TR features and to aid the identification of TRs in genomes, using a program we developed, TRFolder. We applied our method to confirm and improve previously studied core structures from Saccharomyces and Kluyveromyces TRs. We made novel structural predictions of core elements of the TRs from Schizosaccharomyces pombe, Candida albicans, and several other yeast species.